2014
DOI: 10.1111/mcn.12151
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet during early childhood, but not pregnancy, predicts diet quality and fruit and vegetable acceptance in offspring

Abstract: Studies have identified prenatal flavour exposure as a determinant of taste preferences in infants; however, these studies have focused on relatively small samples and limited flavours. As many parents struggle with getting children to accept a variety of nutritious foods, a study of the factors influencing food acceptance is warranted. The objective of this study was to determine whether exposure to a wider variety of fruit and vegetables and overall higher diet quality in utero results in acceptance of a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 40 publications
0
37
0
4
Order By: Relevance
“…The current study builds on the evidence base that mammalian infants learn about the food environment in which they live and their mothers' diet during breastfeeding (13,14,39) and provides further evidence that there is a period during early life when the hedonic response to food flavors experienced in mother's milk can be enhanced. Infants whose mothers drank a variety of vegetable juices, including carrot juice, were more accepting of cereal that was flavored with carrot juice (as determined by intake and rate of feeding) than were infants in the control group whose mothers drank water and avoided intake of the same vegetables.…”
Section: Discussionmentioning
confidence: 90%
“…The current study builds on the evidence base that mammalian infants learn about the food environment in which they live and their mothers' diet during breastfeeding (13,14,39) and provides further evidence that there is a period during early life when the hedonic response to food flavors experienced in mother's milk can be enhanced. Infants whose mothers drank a variety of vegetable juices, including carrot juice, were more accepting of cereal that was flavored with carrot juice (as determined by intake and rate of feeding) than were infants in the control group whose mothers drank water and avoided intake of the same vegetables.…”
Section: Discussionmentioning
confidence: 90%
“…Not surprisingly, maternal diet quality as well as maternal postnatal diet and child diet during infancy and early toddlerhood have been found to be highly correlated. 60–62 Therefore, it remains possible that the observed associations between maternal diet quality and child development are due to the child’s diet after pregnancy. Ultimately, the interpretation of the reported effect sizes depends on the assumed causal model.…”
Section: Resultsmentioning
confidence: 99%
“…Exclusive breastfeeding for at least three months is associated with a higher consumption of vegetables at four years [30]. In particular, it was shown that the maternal dietary variety (especially for the fruit and vegetable group) during early childhood, but not during pregnancy, predicted the acceptance of fruit and vegetables in children [31]. Thus, in addition to breastfeeding, the FV consumption by the mother may be important for enhancing FV acceptance in children.…”
Section: Role Of Previous Mode Of Milk Feedingmentioning
confidence: 99%